2021
DOI: 10.1111/1468-5973.12380
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 lockdown on perceived stress: The role of defence mechanisms and coping strategies

Abstract: The COVID‐19 pandemic represents a unique global challenge. To deter its spread, several countries have put lockdown and physical distancing measures in place that could have potentially harmful consequences on people's mental health. Therefore, the aim of this study is to explore the relationship between anxiety and perceived stress in individuals who were experiencing the COVID‐19 lockdown measures, while also analyzing the impact of coping strategies interacting with defence mechanisms. A sample of 1408 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 89 publications
(103 reference statements)
0
18
0
Order By: Relevance
“…They explore different types of media use and they highlight the potential benefits of music listening on life satisfaction during COVID-19. Similarly, the study of Gori et al (2021) confirms the significant impact of state anxiety levels on perceived stress and shows that positive thinking, spirituality, and conviction can have a strong positive influence on the well-being of individuals.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…They explore different types of media use and they highlight the potential benefits of music listening on life satisfaction during COVID-19. Similarly, the study of Gori et al (2021) confirms the significant impact of state anxiety levels on perceived stress and shows that positive thinking, spirituality, and conviction can have a strong positive influence on the well-being of individuals.…”
Section: Resultsmentioning
confidence: 55%
“…Their results show that the majority of students surveyed exhibits symptoms of depression, anxiety, stress and lower scores for satisfaction with life. In the same vein, Gori et al (2021) seek to explore the relationship between anxiety and perceived stress in individuals during confinement related to COVID-19 in Italy. The authors aim to further investigate and study the role of several variables contributing to subjective distress, with a particular focus on the impact of coping strategies and defense mechanisms in catalyzing or hindering the relationship between anxiety and perceived stress in individuals experiencing COVID-19 lock-in.…”
Section: Resultsmentioning
confidence: 99%
“…As for the relationship between investigated variables and age, in line with the literature, we found that younger age was significantly and positively associated with higher psychological stress 42 and emotion dysregulation. 50 Indeed, the pandemic had a significant influence on mental health 51 , 52 with particularly marked consequences for some subcategories of the population, including young adults. 53 Among young adults, in fact, an increase in both internalizing (eg, withdrawal, somatic complaints, anxiety, and depression) and externalizing (eg, aggressive and rule-breaking behaviors) problems were found.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limitations, this study also proposes novel aspects with valid practical implications. The exploration of the role of anxiety, post-traumatic impairment, mature defences, and their mutual interactions in influencing satisfaction with life offers important information that contributes to enriching the existing literature in this field [ 3 , 12 , 15 , 27 , 46 ]. Although the data were collected during the COVID-19 pandemic, they offer important application insights that can be useful both for emergency management and outside of it.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, among the dimensions influencing life satisfaction, anxiety is one of the most reported during the pandemic: Wang and colleagues [ 14 ] showed that about one-third of the participants in the general Chinese population declared moderate to severe anxiety without significant longitudinal changes in those levels. This, in turn, may lead to a series of cascade reactions that could negatively affect life satisfaction [ 4 , 14 ], as demonstrated by previous research indicating the association between anxiety and functional impairment, unhealthy coping strategies, hopelessness [ 15 , 16 ], and lower quality of life [ 17 ]. Therefore, based on the above empirical evidence, hypothesis 1 is developed as follows:…”
Section: Introductionmentioning
confidence: 99%